Comparison of Efficacy of Gabapentin Versus Cetirizine in Patients with Post-Burn Pruritus - Fayyaz, Hamza; Fayyaz, Laiba (Journal of Postgraduate Medical Institute, 2025)
Objective: To compare the efficacy of gabapentin and cetirizine in the management of post-burn pruritus. Methodology: This was designed as a comparative study carried out in Hayatabad Medical Complex, Peshawar, from September 2020 to February 2021. A total of 100 patients with post-burn pruritus were included in the study. The subjects were randomly assigned by lottery method into one of two groups: Group A: gabapentin group or Group B: cetirizine group. The 50 patients allotted to Group A received gabapentin for their post-burn pruritus, whereas the 50 patients assigned to Group B received cetirizine. The efficacy of both drugs in post-burn pruritus management was noted. Results: The results showed that 90% (n=45) patients in Group A showed a VAS score of zero, i.e. efficacy of gabapentin was 90%. In contrast, only 50% (n=25) patients in Group B showed VAS=0, i.e. the efficacy of cetirizine was 50%. The result was statistically significant. Conclusion: In conclusion, this study noted that management of post-burn pruritus with gabapentin monotherapy was significantly more effective than cetirizine.